2019
DOI: 10.1002/adsc.201801498
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Thermal Activation, Ball‐milling and Aqueous Medium in Stereoselective Michael Addition of Nitromethane to Enynones Catalyzed by Chiral Squaramides

Abstract: Stereoselective addition of nitromethane to conjugated en-ynones was performed through the application of chiral squaramides. Three non-classical approaches to promote the addition reaction were tested, including activation of the nucleophile by inorganic base in a biphasic aqueous system, thermal activation, and ball-milling. Hydrogen-bonding catalysis was effective in all these methods, providing 1,4addition products in high yields and stereoselectivities of up to 98% requiring 1-5 mol% of Cinchona alkaloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Products like alkynyl enones 3g can be difficult to reliably access and control, which is likely why there have only been three reports of their use for enantioselective conjugate additions . We found that these compounds could be enantioselectively transformed into β-branched ketones by subsequently using a chiral diol catalyst (Scheme ).…”
mentioning
confidence: 99%
“…Products like alkynyl enones 3g can be difficult to reliably access and control, which is likely why there have only been three reports of their use for enantioselective conjugate additions . We found that these compounds could be enantioselectively transformed into β-branched ketones by subsequently using a chiral diol catalyst (Scheme ).…”
mentioning
confidence: 99%
“…Moreover, our calculations indicate that the aldehyde group forms hydrogen bonds with the squaramide unit which thus assumes the appropriate position to attack the acceptor (2.48 Å). According to the previous model involving organocatalyzed addition to Michael acceptor, [11] the ketone is believed to interact with the protonated amine. In the alternative orientation of the ketone, that would result in formation of the opposite stereogenic center, the electron poor double bond is away of the reaction center and thus becomes unreachable for the C−S bond formation.…”
Section: Resultsmentioning
confidence: 99%
“…2-(Phenylethynyl)benzaldehyde 1 a-1 c, [7b] 1 d, [27] 1 e, [7b] 1 f, [27] 1 g, [28] 1 h, [29] 1 i, [30] 1 j-1 k, [7b] 1 l, [31] 3-phenylprop-2-yn-1-ol (2 a), [32] 2 b-2 c, [33] 2 d, [34] 2 e-2 h, [33] 2 i, [35] 2 j, [33] 2 k, [36] 1phenyl-1-propyne (7), [37] 8, [38] 12, [20] 13 [20] were prepared according to the literature procedure.…”
Section: Methodsmentioning
confidence: 99%